Ez-crutches: an innovation of axillary crutches for orthopedic client / Suzana Yusof, Norhaini Majid and Noraini Hashim - Yusof, Suzana; Majid, Norhaini; Hashim, Noraini (2020)
Successful management of clients with orthopedic conditions is a critical process that can be compromised by several factors such as late ambulation and rehabilitation. Though the difficulties and complexities of recovery process management are relatively well known and established for any types of fractures, the use of axillary crutches is the most common and convenient as an assistive device. These crutches help the client in early ambulation to support the weak, injured, fractured, or post-operated leg. This project aims to innovate current axillary crutches into the most client-friendly, called Ez-Crutches to enhance the handling of the standard axillary crutches without hustle. An elastic Velcro strap is applied to the standard crutches to secure it whenever the clients lift their hands. Thus, this innovation could prevent the crutches from fall, which leads to difficulty for the clients to pick it up that may cause further injuries. Therefore, this innovative project will be offering a new potential device that enhance the therapeutic intervention in the orthopedic field. This project's extension would be proposed to the Malaysian Orthopedic Association for an endorsement of this Ez-Crutches usage.